On target: Rational approaches to KRAS inhibition for treatment of non-small cell lung carcinoma. (October 2021) - Lindsay, Colin R.; Garassino, Marina C.; Nadal, Ernest; Öhrling, Katarina; Scheffler, Matthias; Mazières, Julien
Highlights: Approximately 30–40% of patients with NSCLC have a KRAS mutation. New targeted therapies for patients with KRAS -mutant NSCLC are emerging. Sotorasib was approved by the FDA in May 2021. Adagrasib received Breakthrough Therapy Designation by the FDA in June 2021. Strong rationale exists for combining direct anti-KRAS agents with other treatments. Abstract: Non-small cell lung carcinoma (NSCLC) is a leading cause of cancer death. Approximately one-third of patients with NSCLC have a KRAS mutation. KRAS G12C, the most common mutation, is found in 13% of patients. While KRAS was long considered 'undruggable', several novel direct KRAS G12C inhibitors have shown encouraging signs of efficacy in phase I/II trials and one of these (sotorasib) has recently been approved by the US Food and Drug Administration. This review examines the role of KRAS mutations in NSCLC and the challenges in targeting KRAS. Based on specific KRAS biology, it reports exciting progress, exploring the use of novel direct KRAS inhibitors as monotherapy or in combination with other targeted therapies, chemotherapy, and immunotherapy.